Encapsulation of Calcium Phosphates on Electrospun Nanofibers for Tissue Engineering Applications - Arputharaj Joseph Nathanael; Tae Hwan Oh (Crystals, 2021)
In the field of tissue engineering, electrospinning is a versatile technique that provides nanofibers with structure similar to that of the extracellular matrix owing to their flexible functionalization. Considerable developments in electrospinning have been made to produce engineered electrospun nanofibers for different biomedical applications. Various biopolymers possess good biocompatibility and biodegradability and are nontoxic in nature. Modification of these biopolymers can enhance or elicit certain properties. One technique of modification is the incorporation of certain inorganic ions or components that can enhance its specific functional characteristics such as mineralization, osseointegration, and bioactivity. Incidentally, calcium phosphate (CaP) materials have proven to be suitable and versatile for biopolymer incorporation and exploration because of their inherent bioactivity and being key mineral constituents of bone and teeth. The addition of CaP materials to polymers enhances cell infiltration, differentiation, and biomineralization. We aim to provide a broad overview of CaP material (particularly hydroxyapatite (HA))-incorporated electrospun nanocomposite fibers and their possible applications in tissue engineering. Some key polymer/HA composites were discussed in detail, and a brief discussion on other polymer/HA composites was also provided. Finally, we discussed the future perspectives of this interesting and emerging composite material fabricated via electrospinning.